Enhancing the practice of social work. (3rd May 2016) - King, Ruth
ABSTRACT: This account of practice focuses on my learning and development as a new Action Learning Facilitator. It reflects on my thoughts and feelings as I began to facilitate my own sets a year or so ago. It will discuss and reflect on topics such as communication, feedback, expectations (both mine, the set members and the organisations), values, ethics, power and confidentiality. It opens with a personal reflection on my experience of becoming a set facilitator and then explores other aspects of my learning. It draws out, in particular, the links between Action Learning and social work and the ways in which the principles that underpin each of these are complementary and mutually enhancing.